Phenotypic heterogeneity and tumor immune microenvironment directed therapeutic strategies in pancreatic ductal adenocarcinoma - Ramesh, Remya P. G.; Yasmin, Hadida; Ponnachan, Pretty; Al-Ramadi, Basel; Kishore, Uday; Joseph, Ann Mary (Frontiers in Immunology, 2025)
Pancreatic cancer is an aggressive tumor with high metastatic potential which leads to decreased survival rate and resistance to chemotherapy and immunotherapy. Nearly 90% of pancreatic cancer comprises pancreatic ductal adenocarcinoma (PDAC). About 80% of diagnoses takes place at the advanced metastatic stage when it is unresectable, which renders chemotherapy regimens ineffective. There is also a dearth of specific biomarkers for early-stage detection. Advances in next generation sequencing and single cell profiling have identified molecular alterations and signatures that play a role in PDAC progression and subtype plasticity. Most chemotherapy regimens have shown only modest survival benefits, and therefore, translational approaches for immunotherapies and combination therapies are urgently required. In this review, we have examined the immunosuppressive and dense stromal network of tumor immune microenvironment with various metabolic and transcriptional changes that underlie the pro-tumorigenic properties in PDAC in terms of phenotypic heterogeneity, plasticity and subtype co-existence. Moreover, the stromal heterogeneity as well as genetic and epigenetic changes that impact PDAC development is discussed. We also review the PDAC interaction with sequestered cellular and humoral components present in the tumor immune microenvironment that modify the outcome of chemotherapy and radiation therapy. Finally, we discuss different therapeutic interventions targeting the tumor immune microenvironment aimed at better prognosis and improved survival in PDAC.